Chapel of Our Lady of Talpa - Wroth, William (Taylor Museum, Colorado Springs, Colorado, 1979)
The history, architecture, and saints of the Chapel of Our Lady of Talpa New Mexico. Includes drawings and plans
57473
Keywords: Chapel of Our Lady of Talpa; Southwest; Santos (Art); Talpa, New Mexico